2018
DOI: 10.1038/s41418-018-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circAGO2 drives cancer progression through facilitating HuR-repressed functions of AGO2-miRNA complexes

Abstract: Argonaute 2 (AGO2), the core component of microRNA (miRNA)-induced silencing complex, plays a compelling role in tumorigenesis and aggressiveness. However, the mechanisms regulating the functions of AGO2 in cancer still remain elusive. Herein, we indentify one intronic circular RNA (circRNA) generated from AGO2 gene (circAGO2) as a novel regulator of AGO2-miRNA complexes and cancer progression. CircAGO2 is up-regulated in gastric cancer, colon cancer, prostate cancer, and neuroblastoma, and is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
215
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(218 citation statements)
references
References 58 publications
1
215
1
1
Order By: Relevance
“…Except as RNA sponge, mounting evidence suggested circRNAs could sequester proteins. 16 Here, we constructed a circFOXO3 interaction protein network. By using RBPDB database, eight RNA binding proteins (MBNL1, NONO, SFRS9, RBM4, SFRS1, FUS, EIF4B and RBMX) with relative score ≥ 0.99 were identified to interact with circFOXO3 ( Figure S1A).…”
Section: Identification Of Circfoxo3 Mediated Cerna and Confirmatiomentioning
confidence: 99%
“…Except as RNA sponge, mounting evidence suggested circRNAs could sequester proteins. 16 Here, we constructed a circFOXO3 interaction protein network. By using RBPDB database, eight RNA binding proteins (MBNL1, NONO, SFRS9, RBM4, SFRS1, FUS, EIF4B and RBMX) with relative score ≥ 0.99 were identified to interact with circFOXO3 ( Figure S1A).…”
Section: Identification Of Circfoxo3 Mediated Cerna and Confirmatiomentioning
confidence: 99%
“…Long noncoding RNA (lncRNAs) and circular RNAs (cir-cRNAs) are important factors in human cancer pathogenesis [15,20,21]. Both lncRNAs and circRNAs lack the ability to encode proteins and circRNAs are characterized by the covalent conjunction and lacking of the 3′ and 5′ end.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate circRNA-miRNA interaction potentials, bioinformatics databases TargetScan (https ://www.targe tscan .org/) and circinteractome (https ://circi ntera ctome .nia.nih.gov/) were used to predict potential binding sites of miRNAs in circENTPD7 [15,16]. The results of this study found that miR-101-3p may be the target of circENTPD7.…”
Section: Circentpd7 Targets Mir-101-3p As a Mirna Spongementioning
confidence: 97%
“…Circular RNAa (circRNAs), a new subtype of ncRNAs, have covalently closed loop structures with a back splice site between 5′-and 3′-end and exhibit higher conservativity than the corresponding linear RNAs duo to resistance to RNase R [7]. Mounting data indicated that circRNAs act critical roles in multiple molecular mechanisms including tumor biomarkers, regulating gene expression, and sponging miRNAs in cancer [8][9][10]. Circ-DONSON [8], circAGO2 [9], circAKT3 [11], circNRIP1 [12], and circDLST [13] are upregulated in GC tissues samples, and their increased expression is associated with TNM stage and poor prognosis in patients with GC [8,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting data indicated that circRNAs act critical roles in multiple molecular mechanisms including tumor biomarkers, regulating gene expression, and sponging miRNAs in cancer [8][9][10]. Circ-DONSON [8], circAGO2 [9], circAKT3 [11], circNRIP1 [12], and circDLST [13] are upregulated in GC tissues samples, and their increased expression is associated with TNM stage and poor prognosis in patients with GC [8,11,13]. CircAKT3 and circDLST act as the sponges of miR-198/-502-5p to favor the tumorigenesis and cisplatin resistance in GC cells [11,13].…”
Section: Introductionmentioning
confidence: 99%